Faktor-faktor yang mempengaruhi minat beli di pasar tradisional - Yulius Laga; Maria Endang Jamu (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This study aims to analyze the variables that influence purchase interest in traditional markets in terms of location, product diversity, price, and service quality variables. This type of research uses a quantitative approach. The research was carried out by comparing the three traditional markets including Wolowona Market, Potulando Market and Mbongawani Market which are located in Ende Regency. The study will be conducted on 270 respondents who are consumers who carry out activities in the three markets who are selected by using the random sampling technique. The research will be conducted by Confirmatory Factor Analysis using Structural Equation Modeling (SEM) with AMOS 23 software. The results show that the three traditional markets have certain characteristics that affect buying interest. In Wolowona Market and Potulando Market, the location variable is the dominant factor affecting buying interest, in contrast to the Mbongawani Market, the price variable is the main reason for people to buy. The recommendation of this research is the need for consideration for traditional market managers in Ende Regency in determining the location and placement of traders according to the product variants sold in the traditional market, as well as price control from the government for the community in meeting their needs.